ANALISIS PERSEPSI MASYARAKAT TERHADAP AKTIVITAS PLTU (PUSAT LISTRIK TENAGA UAP) PAITON DI KECAMATAN PAITON KABUPATEN PROBOLINGGO - Mustofa Mustofa; R Dino Bayu Sagara (RELASI : JURNAL EKONOMI, 2015)
The existence of the area around the power plant (Power Plant Steam) Paiton in District Paiton Probolinggo power plant has been the object of activity, which is carried by Paiton has caused its own problems for society. On the one hand Paiton activity has become one of the economic sources for some people, but this activity has many negative impacts in the form of environmental degradation and changes in people's behavior around Paiton. To lift the local community economy still has enormous economic potential to be developed, namely agriculture, especially tobacco and fishing (fishing) as well as the beach and nature tourism activities .The method used is descriptive qualitative analysis. Data were collected by observation techniques and interviews with structured questions that supported the informant questionnaire enclosed in hearing about the existence of Paiton region, using snowball sampling method. To find a solution in order to lift the local economy both for the existence region directly or indirectly benefit the local community, especially people Paiton districts. As the region closest to the location of the power plant, industry development opportunities based SMEs Supporting local communities to determine the strategy and policy in the development of Supporting Industries conducted a SWOT analysis approach.